2016
DOI: 10.1007/s12528-016-9127-8
|View full text |Cite
|
Sign up to set email alerts
|

“Time is the bottleneck”: a qualitative study exploring why learners drop out of MOOCs

Abstract: Why do over 90% of the learners in Massive Open Online Courses (MOOCs) never finish the course? There is a need for further studies focusing on the learners' experiences of participating in MOOCs and factors that influence the decision to complete or drop out of the course. To deepen our understanding of why learners complete or drop out of MOOCs, we report on a qualitative case study based on in-depth interviews with 34 learners with different degrees of course completion for two MOOCs. A qualitative analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 9 publications
9
111
2
4
Order By: Relevance
“…Some scholars measured students' and instructors' views of MOOCs to identify their experience using MOOCs with different settings (Bruff et al, 2013;Asiri, 2014;Saadatmand & Kumpulainen, 2014;Waite et al, 2013;Patil et al, 2016;Leito et al, 2015;Leito et al, 2015;Eriksson et al, 2017;Salvador & Rodriguez-Hoyos, 2016), perception (Abeera & Miri, 2014;El Turk, 2015;Loizzo, 2015;Saadatmand & Kumpulainen, 2014;Dal Magro et al, 2017;Firmansyah & Timmis, 2016;Mamgain et al, 2014), motivation (Wen et al, 2014;Pickering & Swinnerton, 2017;Atrey et al, 2016;Sooryanarayan & Gupta, 2015), performance (Masanet et al, 2014;Nkuyubwatsi, 2013;Yousef, et al, 2015;Gamage et al, 2015), engagement (Milligan et al, 2013;Pickering & Swinnerton, 2017;Mulumba, 2016), preference (Abeera & Miri, 2014;Mamgain et al, 2014;Atrey et al, 2016), satisfaction (Fidalgo-Blanco et al, 2016;Khalil & Ebner, 2013), interaction (Khalil & Ebner, 2013), behavior (Campbell et al, 2014;Leach & Hadi, 2017), awareness (Bucovetchi et al, 2015), and intent (Campbell et al, 2014). This variation can help the researchers evaluate the MOOC and know more about how MOOCs could become an official method of education in the world.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…Some scholars measured students' and instructors' views of MOOCs to identify their experience using MOOCs with different settings (Bruff et al, 2013;Asiri, 2014;Saadatmand & Kumpulainen, 2014;Waite et al, 2013;Patil et al, 2016;Leito et al, 2015;Leito et al, 2015;Eriksson et al, 2017;Salvador & Rodriguez-Hoyos, 2016), perception (Abeera & Miri, 2014;El Turk, 2015;Loizzo, 2015;Saadatmand & Kumpulainen, 2014;Dal Magro et al, 2017;Firmansyah & Timmis, 2016;Mamgain et al, 2014), motivation (Wen et al, 2014;Pickering & Swinnerton, 2017;Atrey et al, 2016;Sooryanarayan & Gupta, 2015), performance (Masanet et al, 2014;Nkuyubwatsi, 2013;Yousef, et al, 2015;Gamage et al, 2015), engagement (Milligan et al, 2013;Pickering & Swinnerton, 2017;Mulumba, 2016), preference (Abeera & Miri, 2014;Mamgain et al, 2014;Atrey et al, 2016), satisfaction (Fidalgo-Blanco et al, 2016;Khalil & Ebner, 2013), interaction (Khalil & Ebner, 2013), behavior (Campbell et al, 2014;Leach & Hadi, 2017), awareness (Bucovetchi et al, 2015), and intent (Campbell et al, 2014). This variation can help the researchers evaluate the MOOC and know more about how MOOCs could become an official method of education in the world.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…The results showed that a k-means clustering approach is beneficial when comparing combined data from analytics and survey data to differentiate engagement clusters in MOOCs. Eriksson et al (2017) report on their qualitative study exploring the reasons that learners stop engaging with MOOCs. Based in interviews with 34 learners with different degrees of course completion, the results showed that the non-formal character of MOOCs and the unclear outcomes can easily lead to non-committal behavior.…”
Section: Engagement and Study Behaviormentioning
confidence: 99%
“…Eriksson et al [4] put forward in their qualitative study investigating the reason of learners' dropouts that some learners had struggled with understanding the spoken language in the video and occasionally the instructors' accent. The MOOC participants also stated that subtitles in English were helpful.…”
Section: Related Workmentioning
confidence: 99%
“…For example, EMMA, a European MOOC platform, provides MOOCs in multiple European languages 3 . Japanese MOOC platform (JMOOC) stated on their website that since many Japanese are struggling with studying in English, they launched JMOOC to serve the Japanese speaking communities 4 . Nevertheless, ESL speakers continue to pay attention to MOOCs that are offered in English.…”
Section: Introductionmentioning
confidence: 99%